E-NTPDase and E-ADA activities in lymphocytes associated with the immune response of rats experimentally infected with Toxoplasma gondii - Tonin A.A. (2013)
An investigation of E-NTPDase and E-ADA activities in lymphocytes from rats experimentally infected with Toxoplasma gondii was carried out in this study. For this purpose, twenty four adult male Wistar rats were divided in two groups/four subgroups (A1 and A2; B1 and B2-6 animal/each group), with "A" as uninfected and "B" inoculated with T. gondii (RH strain). Sampling was performed on days 5 and 10 post-infection (p.i.), with evaluation of hemogram, immunoglobulins (IgM and IgG) and activity of E-NTPDase and E-ADA in lymphocytes. Enzymes essays showed ATP hydrolysis increased on days 5 (P<0.05) and 10 (P<0.01) p.i., as well as an increase of ADP hydrolysis on day 10 (P<0.01) p.i. E-ADA activity on lymphocytes was also increased in both evaluated periods (P<0.01). Based on E-NTPDase and E-ADA increased activities observed on lymphocytes, it is possible to suggest their involvement in an anti-inflammatory response, consisting of a modulatory response, preventing excessive tissue damage caused by the infection with Toxoplasma gondii. © 2013 Elsevier Inc.